Identifikasi Manajemen Resiko yang diusulkan pada Operasional SME dalam Penerapan Sistem ERP Jangka Panjang. - Dedy Ricardo Serumena; Paulus Haba Lena; Salahudin Robo (Ikatan Ahli Informatika Indonesia (IAII), 2019)
Risk management in business strategic based on the survey that has been done by UKM Ebjed Kaos Factory, Bantul (Yogyakarta) by doing interview directly toward one of the supervisor of the factory which states that the risk in business can affect the part of benefit from the result of their production, it is because in the last few years the results of the expected profits was in fact not stable by applying the strategy, it needs strategy with a frameworks in their ERP system, so that every process of production that has done can have information data which is programmed, analyzed and compared to the risk level of the previous production. All the information data based on their sample of logistic experience in the last few years with an interview approaches model towards 2 from 16 employees, 1 chief inventory staff and the main leader of their UKM factory. The results of this approach Provides almost 80% information that the author needs. Then the author designs and implements a strategy that can generate relevant Information data for the framework of risk management of every logistic area of their UKM. In conclusion, when they’re consider with an efficient strategy, it will surely make a profit for t if every risk faced can be designed and implemented well.